Weyl Almost Periodic Functions in Locally Convex Spaces - Abbas, S.; Fedorov, V. E.; Kostić, M. (Lobachevskii journal of mathematics, 2025)
In this paper, we introduce and analyze several new classes of Weyl -almost periodic type functions , where , is an arbitrary non-empty set, and is a locally convex space over the field of complex numbers. We furnish several structural results and present some applications to the abstract Volterra integro-differential equations in locally convex spaces.